2001
DOI: 10.2460/ajvr.2001.62.1187
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in serum calcium, phosphorus, and vitamin D concentrations in llamas and alpacas

Abstract: Mean vitamin D3 concentration varied by > 6 fold in neonatal and yearling llamas and alpacas and > 3 fold in adult animals as a function of season. These results support the hypothesis that seasonal alterations in vitamin D3 concentrations are a key factor in the development of hypophosphatemic rickets in llamas and alpacas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 14 publications
2
37
0
5
Order By: Relevance
“…92 Similar findings were found in alpacas in two separate reports. 86,91 Camelid breeders in high-risk areas are advised to supplement crias using injectable vitamin D-containing products 2 or 3 times during the winter months to provide 1000 IU/kg body weight. 86 Most products also include vitamins A and E. The effects last approximately 2 months.…”
Section: Flexural Limb Deformitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…92 Similar findings were found in alpacas in two separate reports. 86,91 Camelid breeders in high-risk areas are advised to supplement crias using injectable vitamin D-containing products 2 or 3 times during the winter months to provide 1000 IU/kg body weight. 86 Most products also include vitamins A and E. The effects last approximately 2 months.…”
Section: Flexural Limb Deformitiesmentioning
confidence: 99%
“…Vitamin D 3 production is also seasonal; blood concentrations drop during the winter months because of reduced UV light availability. [90][91][92] Heavy cloud cover reduces UV penetration to Earth's surface. It is believed that reduced exposure to UV radiation at low altitudes and nonequatorial latitudes (i.e., outside of South America) reduces vitamin D activation in skin.…”
Section: Flexural Limb Deformitiesmentioning
confidence: 99%
“…211 In this study, crias born in autumn/winter had lower vitamin D concentrations and were more likely to develop rickets than were those born in summer. 211 The reason may be that these animals receive less vitamin D via the placenta or colostrum because of the low level of solar radiation at that time of year, 182 and a young cria's diet consists substantially of milk, which is low in vitamin D. 211 Interestingly, alpacas appear to be more susceptible to rickets than sheep. In an outbreak in New Zealand, alpacas became hypophosphatemic and developed rickets during winter months (Fig.…”
Section: Llamas and Alpacasmentioning
confidence: 99%
“…25,82,209 When transferred to lower altitudes or higher latitudes where solar radiation is much lower, serum vitamin D concentrations in llamas and alpacas decline to low levels, especially during winter. 182,211 Once vitamin D 3 is formed in the skin, it preferentially binds to vitamin D-binding protein in the capillaries of the dermis, and it is either stored in fat or transported to the liver. 87 Whether obtained from sun exposure or diet, vitamins D 2 and D 3 are biologically inactive and must undergo two hydroxylation reactions to be activated.…”
Section: Biology Of Vitamin D Activation Of Vitamin Dmentioning
confidence: 99%
“…Their serum concentrations had significant differences between three age groups of camels. N egative relationship of age with serum concentration of Pin one-humped camel and llamas (Rezakhani et al 1997, Smith andVan Saun 2001), and with serum Ca and Pi n different breeds of dairy cattle and sheep (Schaffer et al 1981) has been reported. in different breeds of sheep, an age related decrease in serum Ca, P and K, and an increase in serum Mg have been reported (Lane et al 1968).…”
mentioning
confidence: 99%